2014
DOI: 10.1186/1471-2407-14-578
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage inhibitory cytokine 1 (MIC-1/GDF15) as a novel diagnostic serum biomarker in pancreatic ductal adenocarcinoma

Abstract: BackgroundMacrophage inhibitory cytokine 1 (MIC-1/GDF15) has been identified as a potential novel biomarker for detection of pancreatic cancer (PCa). However, the diagnostic value of serum MIC-1 for pancreatic ductal adenocarcinoma (PDAC), particularly for those at the early stage, and the value for treatment response monitoring have not yet been investigated.MethodsMIC-1 expression in tumor tissue was analyzed by RT-PCR from 64 patients with PDAC. Serum MIC-1 levels were detected by ELISA in 1472 participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 37 publications
2
78
1
Order By: Relevance
“…Having shown the tumor-promoting potential of GDF-15 in Ras-MEF cells, we next sought to validate our observations using a tumor model that better recapitulated human disease. A recently published study involving several types of cancers showed that circulating levels of GDF-15 are elevated in patients with pancreatic ductal adenocarcinoma (PDAC) (12). This finding was confirmed by measuring plasma GDF-15 levels from patients with PDAC compared with control subjects whose tissue was obtained from our own institutional pancreatic cancer tissue bank (Supplemental Figure 2A).…”
Section: Ras Mefssupporting
confidence: 63%
See 1 more Smart Citation
“…Having shown the tumor-promoting potential of GDF-15 in Ras-MEF cells, we next sought to validate our observations using a tumor model that better recapitulated human disease. A recently published study involving several types of cancers showed that circulating levels of GDF-15 are elevated in patients with pancreatic ductal adenocarcinoma (PDAC) (12). This finding was confirmed by measuring plasma GDF-15 levels from patients with PDAC compared with control subjects whose tissue was obtained from our own institutional pancreatic cancer tissue bank (Supplemental Figure 2A).…”
Section: Ras Mefssupporting
confidence: 63%
“…Patients utilized as cona dense stroma with infiltration of innate immune cells (35,36). In addition, GDF-15 is highly expressed in PDAC compared with other cancers (12). However, interest in this cytokine has been mostly restricted to its role as a potential biomarker, and therefore no mechanism has been proposed for how this cytokine might function during the development of PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…(9-25) Studies examining the association of other inflammatory cytokines, such as interleukin-6 (IL-6) (10, 22-24, 26) and tumor necrosis factor (TNF)-α,(23, 26, 27) with CRC are limited and inconsistent. Recently, macrophage inhibitory cytokine-1 (MIC-1, also known as growth differentiation factor 15, GDF15), a divergent member of the human transforming growth factor (TGF)-β superfamily and a mediator of the systemic inflammatory response,(28) has been related to development of cancers in various organs,(29-32) including CRC. (33) We recently showed that elevated levels of plasma MIC-1 were associated with higher risk of incident CRC.…”
Section: Introductionmentioning
confidence: 99%
“…This data has been validated using RTPCR to confirm upregulation of mir146a and G-CSF as well as downregulation of BMP-7 in sfRON expressing cells (Supplementary Figure S8). We have previously shown that RON P5P6 isoform is oncogenic, TNFRSF6B (DcR3 protein) prevents TRAIL induced apoptosis [32] and GDF15 (MIC-1 protein) is being investigated as a highly specific marker of pancreatic cancer [33]. GAS1 is a tumor suppressor involved in hedgehog signaling and RUNX3 is a transcription factor that is lost in pancreatic cancer and modulates metastatic potential [34, 35].…”
Section: Resultsmentioning
confidence: 99%